Relationship Between Internet Addiction and Mental Health of B.Ed. Students - Parul Barjo; Nilam Kujur (International Journal For Multidisciplinary Research, 2026)
This study was appointed by the researcher to measure the level of severity of the two following variables (Internet Addiction and Mental Health) in B.Ed. Students separately. This study was also aimed to study the relationship internet addicted and mental health of B.Ed. students of Ranchi District and used the respective research methodologies to research our finding. The objective set was to find out the if there was an existing relationship between the two variables of our study, which was confined to our current Ranchi District. Our hypothesis was also formulated in accordance with the null assumption underlying the objective of the study. Our sample size consisted of 200 B.Ed. students selected randomly from a proper survey method where the proposed study was clearly explained to all the participants present, and with their consent the response was collected via pen and paper method. Also, two standardised tests, which were – (a) Manual For Internet Addiction (IAS): Constructed and Standardized by Mrs. Daman Deep Kaur, Dr. Jose J. Kurisunkal and Dr. Mamta Bakliwal, and (b) Mental Health Inventory by Dr. Jagdish and Dr. A.K.Srivastava were reinforced to make the study more standardized and the result to be more prominent. Our investigation and thorough study came to this conclusion that the students of education had higher levels of internet addiction and mental health. It also came to another shocking revelation that our mental health levels were surprising higher than the internet addiction levels in students of education. On to the subject of relationship, we did came to this conclusion that there is a significant difference between internet addiction and mental health.